The White Pass & Yukon route : the scenic railway of the world / White Pass & Yukon Route - Poole Brothers (White Pass & Yukon Route, 1919)
White Pass & Yukon route -- Map of Alaska, British Columbia and Yukon Territory showing connections of the White Pass & Yukon Route with gold fields of Atlin, White Horse, Klondike and Yukon River points to Cape Nome -- Portions of Alaska, British Columbia and Yukon Territory reached by the White Pass & Yukon Route showing Atlin, White Horse and other mining camps. Color; 1:1:500,000, 1:12,000,000 and 1:700,000